As “riquezas do mundo” – Cobiça e ciência nos jardins botânicos de Caiena e Belém do Pará (1790-1803) - Nívia Pombo (Navigator)
The Botanical Gardens of Belém do Pará were created in 1796 as a warehouse for smuggling plants and seeds from the gardens of Cayenne. The activity managed by the state as part in the reform plans. The greed for those plants and seeds was because of the widespread belief that agriculture would be a tool for economic uplift. All through crop diversification and expansion of production. In times of crisis this action was meant to restore mercantile ties and the realm’s balance of trade.